Catalyst for low-pressure CO2 electroreduction and preparation method and application thereof
By introducing cobalt ions into the DUT-67 carrier and combining trifluoromethyl functional group modification, a hydrophobic microenvironment was constructed, which solved the problem of insufficient research on low-voltage CO2 electrical reduction technology, and achieved the effect of efficient CO2 electrical reduction and reducing CO2 separation costs. Provides a solution for the direct utilization of CO2 in flue gas in coal-fired power plants.
Patent Information
- Application Number
- CN202411380334.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing technology has insufficient research on low-voltage CO2 electrical reduction, which limits the application potential of technology and ignores the possibility of reducing CO2 separation costs from the source, especially in the direct and efficient catalytic conversion of CO2 in flue gas in coal-fired power plants.
By introducing cobalt ions into the DUT-67 support and forming a cobalt phthalocyanine complex, combining trifluoromethyl functional group modification, building a hydrophobic microenvironment, reducing competitive hydrogen evolution reactions, and improving the catalytic conversion efficiency of CO2 to CO, it is prepared for low-pressure CO2 Catalysts for electroreduction.
It realizes efficient CO2 electroreduction reaction under low pressure conditions, reduces the cost of CO2 separation, provides a solution for the direct utilization of CO2 in flue gas, and improves the ability of catalyst separation, circulation and regeneration.
Smart Images

Figure CN119243217A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic materials for controlling atmospheric pollutants, and in particular relates to a catalyst for low-pressure CO2 electroreduction, and a preparation method and application thereof. Background Art
[0002] With the proposal of the "dual carbon" goal of reducing pollution and carbon emissions, green environmental protection has become more and more important to people. CO2 emissions from my country's thermal power industry (more than 80% of which belongs to coal-fired power) account for about 43% of the country's total carbon emissions, and are the largest single source of CO2 emissions. The CO2 content in the flue gas of coal-fired power plants can reach up to 30%. How to store and apply this part of CO2 has become the focus of researchers.
[0003] Currently, one of the ways to treat CO2 is to achieve catalytic reduction of CO2 through electric drive, and most of the research on electric-driven CO2 reduction still focuses on the reaction process under 100% CO2 atmosphere conditions. There is still a lack of research on the more complex low-pressure CO2 electroreduction system in actual industrial environments. This limitation not only limits the direct application potential of the technology, but also ignores the possibility of reducing the cost of CO2 separation from the source. Therefore, exploring and optimizing low-pressure CO2 electroreduction technology can not only effectively reduce the cost of CO2 treatment in industrial emission sources such as coal-fired power plants, but also open up new ways to achieve direct and efficient catalytic conversion of CO2 in flue gas, which is of far-reaching significance for promoting the realization of the "dual carbon" goals. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a catalyst for low-pressure CO2 electroreduction and its preparation method and application, so as to solve the problem of harsh reduction conditions required for electrically driven reduction of CO2 and realize efficient electroreduction reaction of low-pressure CO2.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a catalyst for low-pressure CO2 electroreduction, comprising: Dissolve DUT-67 and cobalt salt in N,N-dimethylformamide and disperse them evenly, and heat them to react to obtain DUT-67-Co; Dissolve DUT-67-Co and phthalonitrile in N,N-dimethylformamide and disperse them uniformly, and heat them to react to obtain CoPc-DUT-67; CoPc-DUT-67 and aromatic or aliphatic carboxylic acid containing a trifluoromethyl functional group are dissolved in an organic solvent and dispersed uniformly, and heated to react to obtain CoPc-DUT-67-F.
[0006] The mass ratio of DUT-67 to cobalt salt is (4-5):10; The heating conditions for preparing DUT-67-Co are: heating at 80~90°C for 12~16 hours.
[0007] The cobalt salt includes CoCl4·6H2O or Co(NO3)2·6H2O.
[0008] The mass ratio of DUT-67-Co to phthalonitrile is 5∶(3~4); The heating conditions for preparing CoPc-DUT-67 are: heating at 180~200℃ for 20~30min.
[0009] The mass ratio of CoPc-DUT-67 to aromatic or aliphatic carboxylic acid containing trifluoromethyl functional group is (2~1):1; The heating conditions for preparing CoPc-DUT-67-F are: heating at 80-90°C for 12-16 hours.
[0010] The aromatic or aliphatic carboxylic acid containing a trifluoromethyl functional group is p-trifluoromethylbenzoic acid, 4-(trifluoromethyl)nicotinic acid, 3-(trifluoromethyl)cinnamic acid or perfluoro-3,5,5'-trimethylhexanoic acid.
[0011] The preparation method of DUT-67 is specifically as follows: The zirconium salt and 2,5-thiophene dicarboxylic acid are dissolved in a mixed solution of N,N-dimethylformamide and N-methylpyrrolidone, dispersed uniformly, heated at 100-120° C. for 70-75 hours, and dried to obtain DUT-67.
[0012] The mass ratio of zirconium salt to 2,5-thiophenedicarboxylic acid is 23:(10-12).
[0013] The present invention also provides a catalyst for low-pressure CO2 electroreduction prepared by the above preparation method.
[0014] The present invention also provides the use of the catalyst for low-pressure CO2 electroreduction in a low-pressure CO2 environment for CO2 electroreduction. Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a catalyst for low-pressure CO2 electroreduction. The present invention first introduces cobalt ions into a DUT-67 carrier, and then introduces a phthalocyanine compound. The cobalt element coordinates with the nitrogen atom on the phthalocyanine ring during the reaction to form a stable cobalt phthalocyanine complex on the DUT-67 carrier, thereby achieving the encapsulation of cobalt phthalocyanine active small molecules, enhancing the durability of the active center while multiplying the homogeneous catalyst, which is beneficial to the separation, circulation and regeneration of the catalyst; and post-modifying the DUT-67 carrier with a trifluoromethyl-containing aromatic or aliphatic carboxylic acid to build a carrier pore hydrophobic microenvironment, thereby reducing the competitive hydrogen evolution reaction in the CO2 electroreduction process and improving the catalytic conversion efficiency of CO2 to CO.
[0015] The catalyst for low-pressure CO2 electroreduction provided by the present invention encapsulates cobalt phthalocyanine active small molecules in a DUT-67 carrier to heterogeneously transform the homogeneous catalyst; then, the advantages of the MOF carrier are utilized to form a microscopic hydrophobic structure in the pores through modification with hydrophobic small molecules, thereby inhibiting the hydrogen evolution reaction that is more likely to occur at the reducing end under low-pressure conditions, thereby achieving an efficient CO2 electroreduction reaction under low-pressure conditions.
[0016] The catalyst for low-pressure CO2 electroreduction provided by the present invention can achieve efficient CO2 electroreduction under low-pressure CO2 conditions, reduce the CO2 separation cost from the source, and provide a solution for the direct utilization of CO2 in flue gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for use in the embodiment: Figure 1 XRD diffraction patterns of DUT-67, CoPc-DUT-67 and CoPc-DUT-67-F prepared in Example 1; Figure 2 Schematic diagram of the contact angles of CoPc-DUT-67 and CoPc-DUT-67-F prepared in Example 1; Figure 3 This is a Faraday efficiency diagram of CO after the catalytic reaction of CoPc-DUT-67 and CoPc-DUT-67-F in Example 1; Figure 4 This is a diagram of the H2 Faraday efficiency after CoPc-DUT-67 and CoPc-DUT-67-F are used for catalytic reaction in Example 1; Figure 5 This is a comparison chart of the Faradaic efficiency of CO at the optimal potential of CoPc-DUT-67-F prepared in Examples 2-4. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] Metal organic frameworks (MOFs) are a type of crystalline porous materials composed of metal nodes and organic ligands bridged by coordination bonds. They have good tailorability and modifiability, and have a clear structure and adjustable pores. They are widely used in adsorption separation, chemical sensing, and heterogeneous catalysis.
[0020] The present invention will be further described below in conjunction with the accompanying drawings: A method for preparing a catalyst for low-pressure CO2 electroreduction comprises the following steps: DUT-67 and cobalt salt were dissolved in N,N-dimethylformamide (DMF) and dispersed evenly, and heated for reaction. After cooling to room temperature, they were washed with DMF and ethanol, and dried to obtain a purple powder, which was recorded as DUT-67-Co. DUT-67-Co and phthalonitrile were dissolved in N,N-dimethylformamide and dispersed evenly, and heated to react. After cooling to room temperature, they were washed with DMF and acetone and dried to obtain a dark green powder, which was recorded as CoPc-DUT-67. CoPc-DUT-67 and aromatic or aliphatic carboxylic acids containing trifluoromethyl functional groups are dissolved in common organic solvents such as methanol and ethanol and dispersed evenly, heated to react, cooled to room temperature, washed with methanol, and dried to obtain a dark green powder, which is recorded as CoPc-DUT-67-F.
[0021] The present invention is further explained below: In some embodiments, the mass ratio of DUT-67 to cobalt salt is (4-5) : 10. It should be noted that if the proportion of cobalt salt added is too high, it may over-occupy the active sites of the DUT-67 carrier, resulting in structural distortion; while if the proportion added is too low, the cobalt ions may not fully exert their enhancing effect on structural stability.
[0022] In some embodiments, the cobalt salt is at least one of CoCl4·6H2O and Co(NO3)2·6H2O.
[0023] In some embodiments, the heating conditions for preparing DUT-67-Co are: heating in an oven at 80-90° C. for 12-16 hours. It should be noted that the provided heating conditions help DUT-67-Co form a stable structure.
[0024] In some embodiments, the mass ratio of DUT-67-Co to phthalonitrile is 5:(3-4). It should be noted that the synthesis of Co phthalocyanine by Co and phthalonitrile has a strict stoichiometric ratio. A ratio lower than this will result in a portion of Co being coordinated on the MOF framework instead of forming Co phthalocyanine small molecules in the pores.
[0025] In some embodiments, the aromatic or aliphatic carboxylic acid containing a trifluoromethyl functional group is p-trifluoromethylbenzoic acid, 4-(trifluoromethyl)nicotinic acid, 3-(trifluoromethyl)cinnamic acid or perfluoro-3,5,5'-trimethylhexanoic acid. It should be noted that the aromatic or aliphatic carboxylic acid containing a trifluoromethyl group constructs a hydrophobic environment in the DUT-67 carrier, which is beneficial to reduce the competitive hydrogen evolution reaction during the CO2 electroreduction process.
[0026] In some embodiments, the heating conditions for preparing CoPc-DUT-67 are: heating at a temperature of 180-200° C. for 20-30 min.
[0027] In some embodiments, the mass ratio of CoPc-DUT-67 to the aromatic or aliphatic carboxylic acid containing a trifluoromethyl functional group is (2-1): 1. It should be noted that due to the limited coordination capacity of the unsaturated Zr cluster in DUT-67, when this ratio is exceeded, the ligand cannot be grafted onto the DUT-67 carrier even if the amount of the ligand is increased after full coordination.
[0028] In some embodiments, the heating conditions for preparing CoPc-DUT-67-F are: heating in an oven at 80-90° C. for 12-16 hours.
[0029] In some embodiments, the preparation method of DUT-67 is specifically: The zirconium salt and 2,5-thiophene dicarboxylic acid were dissolved in a mixed solution of N,N-dimethylformamide and N-methylpyrrolidone and dispersed evenly, and then transferred to a reactor lined with polytetrafluoroethylene, and heated in an oven at 100-120°C for 70-75 hours. After cooling to room temperature, the mixture was washed with DMF and ethanol, and dried to obtain a white powder, which was recorded as DUT-67.
[0030] The mass ratio of the zirconium salt to 2,5-thiophenedicarboxylic acid is 23:(10-12).
[0031] It should be noted that the DUT-67 carrier prepared by the provided preparation method has regular porosity and a large specific surface area, as well as excellent stability.
[0032] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific examples.
[0033] In the following examples, unless otherwise specified, all materials used can be obtained through common channels; and the test methods adopted are conventional methods in the art.
[0034] Example 1 Synthesis of DUT-67: 460 mg ZrCl4 and 220 mg 2,5-thiophenedicarboxylic acid were dissolved in a mixed solution of 25 ml N,N-dimethylformamide (DMF) and 25 ml N-methylpyrrolidone, transferred to a reactor lined with polytetrafluoroethylene, and placed in an oven at 120 °C for 72 hours. After cooling to room temperature, the mixture was washed with DMF and ethanol and dried to obtain a white powder, which was recorded as DUT-67.
[0035] Synthesis of DUT-67-Co: Weigh 40 mg of DUT-67 and 100 mg of CoCl4·6H2O, disperse them in 3 ml of DMF, heat them in an oven at 85°C for 12 hours, cool them to room temperature, wash them with DMF and ethanol, and dry them to obtain a purple powder, which is recorded as DUT-67-Co.
[0036] Synthesis of CoPc-DUT-67: Dissolve 20 mg of DUT-67-Co and 12 mg of phthalonitrile in 2 ml of formamide in a flask, heat to 190°C, maintain for 20 minutes, cool to room temperature, wash with DMF and acetone, and dry to obtain a dark green powder, recorded as CoPc-DUT-67.
[0037] Synthesis of CoPc-DUT-67-F: 20 mg CoPc-DUT-67 and 10 mg p-trifluoromethylbenzoic acid were dispersed in 10 ml methanol and heated in an oven at 85°C for 12 hours. After cooling to room temperature, the mixture was washed with methanol and dried to obtain a dark green powder, which was recorded as CoPc-DUT-67-F.
[0038] DUT-67, DUT-67-Co, CoPc-DUT-67 and CoPc-DUT-67-F prepared in Example 1 were tested. The XRD diffraction patterns of DUT-67, CoPc-DUT-67 and CoPc-DUT-67-F were as follows: Figure 1 As shown; the contact angles of CoPc-DUT-67 and CoPc-DUT-67-F are as follows Figure 2 shown; through Figure 1and Figure 2 It can be seen that the crystal structure of the MOF material DUT-67 was not destroyed during the post-modification process, and the modified material has obvious hydrophobic properties.
[0039] Example 2 Synthesis of DUT-67: 460 mg ZrCl4 and 220 mg 2,5-thiophenedicarboxylic acid were dissolved in a mixed solution of 25 ml N,N-dimethylformamide (DMF) and 25 ml N-methylpyrrolidone, transferred to a reactor lined with polytetrafluoroethylene, and placed in an oven at 120°C for 72 hours. After cooling to room temperature, it was washed with DMF and ethanol and dried to obtain a white powder, which was recorded as DUT-67.
[0040] Synthesis of DUT-67-Co: Weigh 40 mg DUT-67 and 100 mg CoCl4·6H2O, disperse them in 3 ml DMF, heat them in an oven at 85°C for 16 h, cool them to room temperature, wash them with DMF and ethanol, and dry them to obtain a purple powder, which is recorded as DUT-67-Co.
[0041] Synthesis of CoPc-DUT-67: Dissolve 20 mg of DUT-67-Co and 15 mg of phthalonitrile in 2 ml of formamide in a flask, heat to 190°C, maintain for 20 minutes, cool to room temperature, wash with DMF and acetone, and dry to obtain a dark green powder, recorded as CoPc-DUT-67.
[0042] Synthesis of CoPc-DUT-67-F-2: Add 20 mg of CoPc-DUT-67 and 10 mg of 2-(2,2,2-trifluoroethyl)benzoic acid to 10 ml of methanol, heat in an oven at 85 °C for 14 hours, cool to room temperature, wash with methanol, and dry to obtain a dark green powder, recorded as CoPc-DUT-67-F-2.
[0043] Example 3 Synthesis of DUT-67: 460 mg ZrCl4 and 220 mg 2,5-thiophenedicarboxylic acid were dissolved in a mixed solution of 25 ml N,N-dimethylformamide (DMF) and 25 ml N-methylpyrrolidone, transferred to a reactor lined with polytetrafluoroethylene, and placed in an oven at 120 °C for 72 hours. After cooling to room temperature, the mixture was washed with DMF and ethanol and dried to obtain a white powder, which was recorded as DUT-67.
[0044] Synthesis of DUT-67-Co: Weigh 40 mg DUT-67 and 100 mg CoCl4·6H2O, disperse them in 3 ml DMF, heat them in an oven at 85°C for 14 h, cool them to room temperature, wash them with DMF and ethanol, and dry them to obtain a purple powder, which is recorded as DUT-67-Co.
[0045] Synthesis of CoPc-DUT-67: Dissolve 20 mg of DUT-67-Co and 12 mg of phthalonitrile in 2 ml of formamide in a flask, heat to 190°C, maintain for 30 minutes, cool to room temperature, wash with DMF and acetone, and dry to obtain a dark green powder, recorded as CoPc-DUT-67.
[0046] Synthesis of CoPc-DUT-67-F-3: Add 20 mg of CoPc-DUT-67 and 20 mg of trifluoromethylbenzoic acid to 10 ml of methanol, heat in an oven at 85°C for 16 hours, cool to room temperature, wash with methanol, and dry to obtain a dark green powder, recorded as CoPc-DUT-67-F-3.
[0047] Example 4 Synthesis of DUT-67: 460 mg ZrCl4 and 220 mg 2,5-thiophenedicarboxylic acid were dissolved in a mixed solution of 25 ml N,N-dimethylformamide (DMF) and 25 ml N-methylpyrrolidone, transferred to a reactor lined with polytetrafluoroethylene, and placed in an oven at 120 °C for 72 hours. After cooling to room temperature, the mixture was washed with DMF and ethanol and dried to obtain a white powder, which was recorded as DUT-67.
[0048] Synthesis of DUT-67-Co: Weigh 40 mg of DUT-67 and 100 mg of Co(NO3)2·6H2O, disperse them in 3 ml of DMF, heat them in an oven at 85°C for 16 hours, cool to room temperature, wash with DMF and ethanol, and dry to obtain a purple powder, which is recorded as DUT-67-Co.
[0049] Synthesis of CoPc-DUT-67: Dissolve 20 mg of DUT-67-Co and 12 mg of phthalonitrile in 2 ml of formamide in a flask, heat to 200°C, maintain for 25 minutes, cool to room temperature, wash with DMF and acetone, and dry to obtain a dark green powder, recorded as CoPc-DUT-67.
[0050] Synthesis of CoPc-DUT-67-F-4: Add 20 mg of CoPc-DUT-67 and 20 mg of trifluoromethylbenzoic acid to 10 ml of methanol, heat in an oven at 85°C for 16 hours, cool to room temperature, wash with methanol, and dry to obtain a dark green powder, recorded as CoPc-DUT-67-F-4.
[0051] Example 5 Synthesis of DUT-67: 460 mg ZrCl4 and 240 mg 2,5-thiophene dicarboxylic acid were dissolved in a mixed solution of 25 ml N,N-dimethylformamide (DMF) and 25 ml N-methylpyrrolidone, transferred to a reactor lined with polytetrafluoroethylene, placed in an oven at 120 °C for 75 hours, cooled to room temperature, washed with DMF and ethanol, and dried to obtain a white powder, recorded as DUT-67.
[0052] Synthesis of DUT-67-Co: Weigh 40 mg of DUT-67 and 100 mg of Co(NO3)2·6H2O, disperse them in 3 ml of DMF, heat them in an oven at 90°C for 16 hours, cool to room temperature, wash with DMF and ethanol, and dry to obtain a purple powder, which is recorded as DUT-67-Co.
[0053] Synthesis of CoPc-DUT-67: Dissolve 20 mg of DUT-67-Co and 16 mg of phthalonitrile in 2 ml of formamide in a flask, heat to 200°C, maintain for 25 minutes, cool to room temperature, wash with DMF and acetone, and dry to obtain a dark green powder, recorded as CoPc-DUT-67.
[0054] Synthesis of CoPc-DUT-67-F-4: Add 20 mg of CoPc-DUT-67 and 20 mg of 4-(trifluoromethyl)nicotinic acid to 10 ml of methanol, heat in an oven at 85°C for 16 hours, cool to room temperature, wash with methanol, and dry to obtain a dark green powder, recorded as CoPc-DUT-67-F-5.
[0055] Example 6 Synthesis of DUT-67: 460 mg ZrCl4 and 200 mg 2,5-thiophene dicarboxylic acid were dissolved in a mixed solution of 25 ml N,N-dimethylformamide (DMF) and 25 ml N-methylpyrrolidone, transferred to a reactor lined with polytetrafluoroethylene, and placed in an oven at 120 °C for 70 hours. After cooling to room temperature, the mixture was washed with DMF and ethanol and dried to obtain a white powder, which was recorded as DUT-67.
[0056] Synthesis of DUT-67-Co: Weigh 50 mg of DUT-67 and 100 mg of Co(NO3)2·6H2O, disperse them in 3 ml of DMF, heat them in an oven at 80°C for 14 hours, cool them to room temperature, wash them with DMF and ethanol, and dry them to obtain a purple powder, which is recorded as DUT-67-Co.
[0057] Synthesis of CoPc-DUT-67: Dissolve 20 mg of DUT-67-Co and 14 mg of phthalonitrile in 2 ml of formamide in a flask, heat to 180°C, maintain for 25 minutes, cool to room temperature, wash with DMF and acetone, and dry to obtain a dark green powder, recorded as CoPc-DUT-67.
[0058] Synthesis of CoPc-DUT-67-F-4: Add 40 mg CoPc-DUT-67 and 20 mg 3-(trifluoromethyl)cinnamic acid to 10 ml methanol, heat in an oven at 85°C for 16 hours, cool to room temperature, wash with methanol, and dry to obtain a dark green powder, recorded as CoPc-DUT-67-F-6.
[0059] Example 7 Synthesis of DUT-67: 460 mg ZrCl4 and 240 mg 2,5-thiophene dicarboxylic acid were dissolved in a mixed solution of 25 ml N,N-dimethylformamide (DMF) and 25 ml N-methylpyrrolidone, transferred to a reactor lined with polytetrafluoroethylene, and placed in an oven at 110 °C for 70 hours. After cooling to room temperature, the mixture was washed with DMF and ethanol and dried to obtain a white powder, which was recorded as DUT-67.
[0060] Synthesis of DUT-67-Co: Weigh 40 mg of DUT-67 and 100 mg of Co(NO3)2·6H2O, disperse them in 3 ml of DMF, heat them in an oven at 90°C for 16 hours, cool to room temperature, wash with DMF and ethanol, and dry to obtain a purple powder, which is recorded as DUT-67-Co.
[0061] Synthesis of CoPc-DUT-67: Dissolve 20 mg of DUT-67-Co and 16 mg of phthalonitrile in 2 ml of formamide in a flask, heat to 190°C, maintain for 25 minutes, cool to room temperature, wash with DMF and acetone, and dry to obtain a dark green powder, recorded as CoPc-DUT-67.
[0062] Synthesis of CoPc-DUT-67-F-4: Add 30 mg of CoPc-DUT-67 and 20 mg of trifluoromethylbenzoic acid to 10 ml of methanol, heat in an oven at 85°C for 16 hours, cool to room temperature, wash with methanol, and dry to obtain a dark green powder, recorded as CoPc-DUT-67-F-7.
[0063] Electrocatalytic low-pressure CO2 reduction reaction All the catalysts prepared in Examples 1-4 were applied to the electroreduction of low-pressure CO2, and the specific operation was as follows: In the H-type electrolytic cell, the electrolyte was 0.5 mol / L KHCO3 solution, and a three-electrode system was used (Ag / AgCl electrode as the reference electrode, Pt electrode as the counter electrode, and the catalyst coated on carbon paper as the working electrode). The CO2 electroreduction performance of CoPc-DUT-67 and CoPc-DUT-67-F was tested under the mixed gas conditions of 30% CO2+70% N2.
[0064] like Figure 3 and Figure 4 As shown, the catalytic results show that CoPc-DUT-67-F, which constructs a microscopic hydrophobic pore structure, reaches the optimal potential at -1.0 V (vs standard hydrogen electrode (RHE)), at which the Faradaic efficiency (FE) of CO is 94.7%, while the Faradaic efficiency of CO of CoPc-DUT-67, which simply encapsulates the active sites, is only 84.2% at the optimal potential.
[0065] like Figure 5 As shown in the figure, the Faradaic efficiency of CO at the optimal potential of CoPc-DUT-67-F-2 is 86.5%, which is not as good as 94.7% of CoPc-DUT-67-F. The reason is that the 2-(2,2,2-trifluoroethyl)benzoic acid has a longer length and a larger molecular volume. While constructing a hydrophobic microenvironment, it blocks the MOF pores more seriously, reduces the microscopic specific surface area of the catalyst, and makes it more difficult for the active site to contact the substrate.
[0066] like Figure 5 The Faradaic efficiencies of CO for CoPc-DUT-67-F-3 and CoPc-DUT-67-F-4 at the optimal potential were 92.1% and 94.0%, respectively, both exceeding 90%.
[0067] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0068] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.
Claims
1. A method for preparing a catalyst for low-pressure CO2 electroreduction, characterized in that: include: Dissolve DUT-67 and cobalt salt in N,N-dimethylformamide and disperse them evenly, and heat them to react to obtain DUT-67-Co; Dissolve DUT-67-Co and phthalonitrile in N,N-dimethylformamide and disperse them uniformly, and heat them to react to obtain CoPc-DUT-67; CoPc-DUT-67 and aromatic or aliphatic carboxylic acid containing a trifluoromethyl functional group are dissolved in an organic solvent and dispersed uniformly, and heated to react to obtain CoPc-DUT-67-F.
2. The method for preparing a catalyst for low-pressure CO2 electroreduction according to claim 1, characterized in that: The mass ratio of DUT-67 to cobalt salt is (4-5):10; The heating conditions for preparing DUT-67-Co are: heating at 80~90°C for 12~16 hours.
3. The method for preparing a catalyst for low-pressure CO2 electroreduction according to claim 1, characterized in that: The cobalt salt includes CoCl4·6H2O or Co(NO3)2·6H2O.
4. The method for preparing a catalyst for low-pressure CO2 electroreduction according to claim 1, characterized in that: The mass ratio of DUT-67-Co to phthalonitrile is 5∶(3~4); The heating conditions for preparing CoPc-DUT-67 are: heating at 180~200℃ for 20~30min.
5. The method for preparing a catalyst for low-pressure CO2 electroreduction according to claim 1, characterized in that: The mass ratio of CoPc-DUT-67 to aromatic or aliphatic carboxylic acid containing trifluoromethyl functional group is (2~1):1; The heating conditions for preparing CoPc-DUT-67-F are: heating at 80-90°C for 12-16 hours.
6. The method for preparing a catalyst for low-pressure CO2 electroreduction according to claim 1, characterized in that: The aromatic or aliphatic carboxylic acid containing a trifluoromethyl functional group is p-trifluoromethylbenzoic acid, 4-(trifluoromethyl)nicotinic acid, 3-(trifluoromethyl)cinnamic acid or perfluoro-3,5,5'-trimethylhexanoic acid.
7. The method for preparing a catalyst for low-pressure CO2 electroreduction according to claim 1, characterized in that: The preparation method of DUT-67 is specifically as follows: The zirconium salt and 2,5-thiophene dicarboxylic acid are dissolved in a mixed solution of N,N-dimethylformamide and N-methylpyrrolidone, dispersed uniformly, heated at 100-120° C. for 70-75 hours, and dried to obtain DUT-67.
8. The method for preparing a catalyst for low-pressure CO2 electroreduction according to claim 7, characterized in that: The mass ratio of zirconium salt to 2,5-thiophenedicarboxylic acid is 23:(10-12).
9. A catalyst for low-pressure CO2 electroreduction prepared according to the preparation method according to any one of claims 1 to 8.
10. The catalyst for low-pressure CO2 electroreduction according to claim 9 is used in CO2 electroreduction in a low-pressure CO2 environment.
Citation Information
Cited By
Sulfonic acid group modified Ni-NC catalyst as well as preparation method and application thereof
CN122564634A
